The Challenges and Opportunities for Shared Decision Making Highlighted by COVID-19 - Abrams, Elissa M. (J Allergy Clin Immunol Pract, 2020)
Shared decision making (SDM) is a management paradigm that empowers patients as partners in their own care in a bidirectional exchange of information and values, and optimize the decision-making process. During the current coronavirus disease 2019 pandemic, there is a greater need to encourage participation in the SDM process. The pandemic has created both challenges and opportunities for delivering care, as system adaptations influence the physician-patient relationship. Although social distancing and health service reallocation can interfere with preference for an in-person visit, these measures also provide an avenue to study and implement virtual SDM processes. Communicating risk at a time of heightened uncertainty may pose a barrier to SDM engagement but provides the opportunity to foster a patient-centered approach within a more personalized context. Social media influence during coronavirus disease 2019 has resulted in an “infodemic” but highlights the importance of patient engagement. The pandemic has changed how we deliver care but allows us to re-evaluate common practices and enhance effectiveness of our management strategies. Navigating the uncertainty of subsequent pandemic waves creates confusion about how to safely reinitiate clinical service. This will require ongoing SDM with our patients and among colleagues through current—and future—challenges. Coronavirus disease 2019 has created many difficulties but has forced us to reexamine how to provide more patient-centered and high-quality care.